AMPLIFICATION OF pncA GENES FROM WATER BACTERIAL POST MINING IN SAMARINDA - Suryadi, Ahmad; Astuti, Winni; Kartika, Rudi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Amplification of pncA genes from water bacterial post mining in Samarinda has been done. The aim of this research is to isolate chromosomal DNA and amplificated the pncA gene from water bacterial post mining in Samarinda. The research methode consist of chromosomal DNA isolation and amplification of pncA gene with polymerase chain reaction (PCR) technique. The result showed the size of chromosomal DNA is ± 10 kb. By using primer pncA gene, the result of amplification of the pncA gene showed that there were two sizes of amplicon, namely 0.7 kb and 0.2 kb. The conclusion that can be drawn was there is two sizes of amplicon pncA gene. Keywords: chromosomal DNA isolation, amplification of pncA gen, PCR